Event generator tunes obtained from underlying event and multiparton scattering measurements - Khachatryan, V. (2016)
New sets of parameters (tunes)for the underlying-event (UE) modelling of the PYTHIA8, PYTHIA6 and HERWIG++ MonteCarlo event generators are constructed using different parton distribution functions. Combined fits to CMS UE proton-proton (pp) data at root s = 7 TeV and to UE proton-antiproton (p (P) over bar) data from the CDF experiment at lower root s, are used to study the UE models and constrain their parameters, providing thereby improved predictions for proton-proton collisions at 13 TeV. In addition, it is investigated whether the values of the parameters obtained from fits to UE observables are consistent with the values determined from fitting observables sensitive to double-parton scattering processes. Finally, comparisons are presented of the UE tunes to minimum bias (MB) events, multijet, and Drell-Yan (q (Q) over bar -> Z/gamma* -> lepton-antilepton+jets) observables at 7 and 8 TeV, as well as predictions for MB and UE observables at 13 TeV.